Changes in functional composition and diversity of waterbirds: The roles of water level and submerged macrophytes. (2nd June 2020) - Özgencil, İbrahim Kaan; Beklioğlu, Meryem; Özkan, Korhan; Tavşanoğlu, Çağatay; Fattorini, Niccolò
Abstract: Water level and submerged macrophytes are critical players for the functioning of shallow lake ecosystems; understanding how waterbird communities respond to changes in both can have important implications for conservation and management. Here, we evaluated the effects of changes in water level and submerged macrophyte status on wintering waterbird community size, functional group abundances, functional diversity (FD), and community assembly by using a dataset compiled over 50 years. We built generalised linear models to evaluate the effects of water level and submerged macrophyte status on the above‐listed attributes of the waterbird communities by using mid‐winter waterbird censuses, water level measurements, and submerged macrophyte surveys, along with submerged macrophyte macrofossil records from two shallow lakes in Turkey. Using a relevant set of functional traits, we defined functional groups, calculated four FD measures, and simulated null distributions of the FD measures for assessing assembly rules. We found that macrophyte‐dominated years had significantly higher abundances of waterbirds in one of the study lakes, and had more diving herbivores and omnivores in both lakes, while diving/scooping fish‐eating waterbird abundance was lower in macrophyte‐dominated years. Community size in Lake Beyşehir exhibited a negative association with water level; surprisingly, however, none of the functional group abundances and FD indices were significantly related to water level. In our study communities, standardised effect sizes of functional richness and functional dispersion—two indices that are particularly sensitive to community assembly processes—were mostly lower than those of randomly assembled communities, which implies functional clustering. Shifts to a scarce‐macrophyte state were associated with increases in these two indices, possibly due to either changes in the relative strength of environmental filtering and limiting similarity in community assembly or sampling of transitional communities. Further studies covering a wider range of the trophic/macrophyte status spectrum are needed to be certain. The results of this study indicate that shifts between abundant and scarce‐macrophyte states can have significant effects on wintering waterbird abundances, FD and community assembly. The results also suggest that shallow lakes in macrophyte‐dominated states can support more wintering waterbirds, especially diving omnivores, some of which are globally threatened.